Orbitofrontal Gray Matter Relates to Early Morning Awakening: A Neural Correlate of Insomnia Complaints? - Stoffers, Diederick; Moens, Sarah; Benjamins, Jeroen; van Tol, Marie-José; Penninx, Brenda W.; Veltman, Dick J.; Van Der Wee, Nic J.; VanSomeren, E J. (Frontiers in Neurology, 2012)
Sleep complaints increase profoundly with age; prevalence estimates of insomnia in elderly people reach up to 37%. The three major types of nocturnal complaints are difficulties initiating sleep (DIS), difficulties maintaining sleep (DMS) and early morning awakening (EMA), of which the latter appears most characteristic for aging. The neural correlates associated with these complaints have hardly been investigated, hampering the development of rational treatment and prevention. A recent study on structural brain correlates of insomnia showed that overall severity, but not duration, of insomnia complaints is associated with lower gray matter (GM) density in part of the left orbitofrontal cortex. Following up on this, we investigated, in an independent sample of people not diagnosed with insomnia, whether individual differences in GM density are associated with differences in DIS, DMS and EMA. 65 healthy participants filled out questionnaires and underwent structural magnetic resonance imaging. Three compound Z-scores were computed for questionnaire items relating to DIS, DMS and EMA. Whole-brain voxel-based morphometry was used to investigate their association with GM density. Results show that participants with lower GM density in a region where the left inferior orbitofrontal cortex borders the insula report more EMA, but not DIS or DMS. This is the first study to investigate structural brain correlates of specific sleep characteristics that can translate into complaints in insomniacs. The selective association of EMA with orbitofrontal GM density makes our findings particularly relevant to elderly people, where EMA represents the most characteristic complaint. It is hypothesized that low GM density in aforementioned orbitofrontal area affects its role in sensing comfort. An intact ability to evaluate comfort may be crucial to maintain sleep, especially at the end of the night when sleep is vulnerable because homeostatic sleep propensity has dissipated.